2020
DOI: 10.3389/fonc.2020.00712
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Exposure of Early-Transformed Human Mammary Cells to Low Doses of Benzo[a]pyrene and/or Bisphenol A Enhances Their Cancerous Phenotype via an AhR/GPR30 Interplay

Abstract: Donini et al. Pollutants Impact Breast Cancer Progression capable of inhibiting carcinogenesis associated with chronic exposure to low doses of B[a]P and BPA in MCF10AT1 cells. Altogether, our results indicate that the engagement of both AhR and GPR30 functions, in particular in an ER-negative/triple-negative context of breast cells, favors tumor progression and leads to poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 86 publications
2
12
0
Order By: Relevance
“…BPs might exert their impact on genotoxicity of a carcinogen through modulating CYP enzymes required for its activation. More importantly, the above impact of BP compounds occurred at levels ranging from 0.1 (or 1) to 100 nM, low enough to fall into the range of the real human plasma levels. , This finding appears consistent with a recent report that long-term exposure of early transformed human mammary cells to BaP and BPA at a very low concentration (0.1 nM) synergistically enhanced their cancerous phenotype via an AhR/G protein-coupled receptor 30 . Moreover, human exposure to BPs is not limited to a single BP compound, while multiple BPs may be present in human bodies; thus, combined effects of BPs, such as BPA, BPF, BPS, and BPAF may lead to amplified effect of BPs.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…BPs might exert their impact on genotoxicity of a carcinogen through modulating CYP enzymes required for its activation. More importantly, the above impact of BP compounds occurred at levels ranging from 0.1 (or 1) to 100 nM, low enough to fall into the range of the real human plasma levels. , This finding appears consistent with a recent report that long-term exposure of early transformed human mammary cells to BaP and BPA at a very low concentration (0.1 nM) synergistically enhanced their cancerous phenotype via an AhR/G protein-coupled receptor 30 . Moreover, human exposure to BPs is not limited to a single BP compound, while multiple BPs may be present in human bodies; thus, combined effects of BPs, such as BPA, BPF, BPS, and BPAF may lead to amplified effect of BPs.…”
Section: Resultssupporting
confidence: 88%
“…14,69 This finding appears consistent with a recent report that long-term exposure of early transformed human mammary cells to BaP and BPA at a very low concentration (0.1 nM) synergistically enhanced their cancerous phenotype via an AhR/G protein-coupled receptor 30. 70 Moreover, human exposure to BPs is not limited to a single BP compound, while multiple BPs may be present in human bodies; 15 thus, combined effects of BPs, such as BPA, BPF, BPS, and BPAF may lead to amplified effect of BPs. An example for such behavior is the additive induction of AhR and CYP1A1 in HepG2 cells by a mixture of BPs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Previous studies have shown that some nuclear receptors are target genes of BPA, such as androgen receptor 45 (AR), estrogen receptor 1 (ESR1), estrogen receptor 2 46 (ESR2), and aryl hydrocarbon receptor 47 (AHR). In our results, all of the aforementioned four genes were predicted as top 100 interactive genes for BPA.…”
Section: Discussionmentioning
confidence: 99%
“…BPA belongs to the endocrine disrupting class of chemicals, and low dose BPA can impact reproduction, the immune system, and is related to hormone-dependent cancers 22 . Previous studies have shown that some nuclear receptors are target genes of BPA, such as androgen receptor 28 ( AR ), estrogen receptor 1 ( ESR1 ), estrogen receptor 2 29 ( ESR2 ), and aryl hydrocarbon receptor 30 ( AHR ). In our results, all of the aforementioned four genes were predicted as top 100 interactive genes for BPA.…”
Section: Discussionmentioning
confidence: 99%
“…These include in vitro ERα-mediated effects of BPA and its analogues on the upregulation of genes involved in cell growth, migration, invasion and cancer development [139], and low doses BPA-induced phosphorylation of its functional non-genomic target Protein Kinase D1 (PKD1), which mediates cell proliferation and anchorage-independent growth in BC cells [140]. Moreover, BPA oncogenic potential regarding BC is also found in its ability to enhance GPER-induced cancerous phenotype [141] and focal adhesion assembly through focal adhesion kinase (FAK), Src and ERK2 in a triple-negative BC model [142]. Others have shown that exposure to xenoestrogens like BPA can increase adult prostate size and induce PC [143].…”
Section: Bisphenolsmentioning
confidence: 99%